Dairy goats successfully introduced in Tanzania - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Norwegian Landrace (NL) crossbred dairy goats are performing exceptionally well in the highlands of Tanzania. In 1983/84, 63 kids of the Norwegian Landrace breed were imported by the experimental farm of the Sokoine University of Agriculture at...